Exploring pathways for gender-responsive climate services in Rwanda - Nsengiyumva, Gloriose; Kagabo, Desire; Gumucio, Tatiana (2018)
A recent study suggests that women are significantly less aware of climate information than men in all provinces of Rwanda (Coulibaly et al., 2017). This gap may be associated with ownership of communication assets and participation in social groups as means of communication of the information where women are far behind men (Coulibaly et al., 2017). In Rwandan agriculture, women represent the highest proportion (90.8% by NISR, 2013), therefore increasing access and uptake of climate information among women will improve their planning and farm management decisions.